2009
DOI: 10.1152/japplphysiol.91551.2008
|View full text |Cite
|
Sign up to set email alerts
|

Aging, exercise, and muscle protein metabolism

Abstract: Koopman R, van Loon LJ. Aging, exercise, and muscle protein metabolism. J Appl Physiol 106: 2040 -2048. First published January 8, 2009 doi:10.1152/japplphysiol.91551.2008Aging is accompanied by a progressive loss of skeletal muscle mass and strength, leading to the loss of functional capacity and an increased risk of developing chronic metabolic disease. The age-related loss of skeletal muscle mass is attributed to a disruption in the regulation of skeletal muscle protein turnover, resulting in an imbalance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
213
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(230 citation statements)
references
References 133 publications
(164 reference statements)
8
213
2
7
Order By: Relevance
“…Disuse muscle atrophy and weakness are causes of impaired function in older individuals [74][75][76][77][78] . While age-related sarcopenia has been repeatedly documented, the effect of aging on tendon biomechanical properties is inconclusive 74,[79][80][81][82][83] .…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disuse muscle atrophy and weakness are causes of impaired function in older individuals [74][75][76][77][78] . While age-related sarcopenia has been repeatedly documented, the effect of aging on tendon biomechanical properties is inconclusive 74,[79][80][81][82][83] .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…While age-related sarcopenia has been repeatedly documented, the effect of aging on tendon biomechanical properties is inconclusive 74,[79][80][81][82][83] . Methodological differences make study comparisons difficult, although the majority of investigators have suggested that collagen loss occurs in older individuals [84][85][86] .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The normal aging process has a profound effect on the structure and function of skeletal muscle. Aged muscle undergoes progressive atrophy, with a decrease in cross-sectional area caused by a decrease in muscle fiber number and fiber size (24,29). Muscle function also appears to be reduced in aged muscle, displaying a decrease in power and maximum force production (6).…”
mentioning
confidence: 99%
“…Although the biochemical and molecular mechanisms responsible for the loss of muscle during aging are not fully understood, 2,3) the loss of muscle during aging is known to be the result of both decreased protein synthesis and increased protein degradation. 34,35) Currently, protection against or prevention of sarcopenia is exercise and eating proper nutrition. Exercise, specifically resistance training or strength training, increases muscle strength and endurance.…”
Section: Discussionmentioning
confidence: 99%